Expanded View of Ultimate Questions in Public Communication of Science: Qualitative Discourse Analysis of Genetics and Neuroscience - Nicoli, Benedetta (Journal for the scientific study of religion, 2024)
This article argues that studying ultimate questions as “potential mediators” of religious worldviews increases sociological knowledge of religion outside institutional boundaries, as research on secularization indicates. Concurrently, other studies demonstrate that the public communication of science (PCS) influences public orientations toward religion. Integrating these contributions, I deploy a qualitative discourse analysis of 78 genetics and neuroscience PCS monographs to investigate whether and how they raise and discuss ultimate questions together with religious references. The analysis reveals two models for relating science and religion in PCS, conflict and integration, and indicates that the latter prevails. Within the integration model, I conceptualize the “expanded view” of ultimate questions in PCS and discuss in detail its main features, especially its nondualistic approach. Lastly, I discuss the possible social consequences of the expanded view and the contribution of my findings to the sociology of religion and the sociology of religion and science.